A Population-Based Evaluation of Depression Symptoms and Hypothyroidism - Saad Ali Khan, Lala Naeem Butt, Nayab Sarwar, Ambreen Ali, Muhammad Habib Khan, Alia Banori, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Findings in sub-clinical situations are inconsistent, despite the fact that overt hypothyroidism is often accepted as a primary cause of depression Material and Methods: In a population-based research of 1298 middle-aged women residing in Peshawar , we looked at the link between hypothyroidism and depressive symptoms Results: 45.7 percent of the participants had depressed symptoms, and 12.3% had hypothyroidism. Women with TSH>10 mUI/ml had a twofold likelihood of presenting depressive symptoms compared to those with normal TSH levels, according to a multiple logistic regression study that controlled for age, BMI and smoking. The adjusted OR was 8.7 among individuals with clinical hypothyroidism. Conclusion: In the general population, TSH levels over a particular threshold have been related to an increased risk of depression. As a result, depression symptoms should be examined in thyroid dysfunction patients, and sad individuals should have their TSH levels checked.